2018
DOI: 10.1016/j.preghy.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Preeclamptic plasma stimulates the expression of miRNAs, leading to a decrease in endothelin-1 production in endothelial cells

Abstract: Preeclampsia is a major cause of maternal and fetal morbidity and mortality worldwide. It is a multisystem pregnancy syndrome characterized by general endothelial dysfunction caused mainly by plasma factors and debris in endothelial cells. It is widely accepted that endothelin-1 (ET-1) is involved in the pathophysiology of preeclampsia, and so it is of interest to ascertain whether the ET-1 gene (EDN1) can be targeted with tools such as miRNAs. Therefore, we investigated the relationship between the expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 45 publications
(74 reference statements)
0
10
0
Order By: Relevance
“…Furthermore, overexpression of let-7 in endothelial cells from PE notably correlated with the expression of genes related to endothelial dysfunction and pathophysiology development, suggesting a critical role of let-7 in PE. 28 In addition, low expression of FOXO1 was found in villous trophoblasts, while overexpression of FOXO1 contributed to abnormal trophoblast differentiation and inhibition of apoptosis in mild and severe PE. 29 More importantly, an increase of FOXO1 was reported to promote adhesion and migration of trophoblast cells, thus preventing the progression of PE.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, overexpression of let-7 in endothelial cells from PE notably correlated with the expression of genes related to endothelial dysfunction and pathophysiology development, suggesting a critical role of let-7 in PE. 28 In addition, low expression of FOXO1 was found in villous trophoblasts, while overexpression of FOXO1 contributed to abnormal trophoblast differentiation and inhibition of apoptosis in mild and severe PE. 29 More importantly, an increase of FOXO1 was reported to promote adhesion and migration of trophoblast cells, thus preventing the progression of PE.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs impact on the posttranscriptional regulation of the ET‐1 gene (EDN1) . In human umbilical vein endothelial cell (HUVEC) incubated with plasma in PE women, resulting in an elevated level of miRNAs 125a, 125b, Let‐7a, Let‐7b, and Let‐7c . As well as Dias et al demonstrated that ET‐1 level was significantly decreased (approximately 25%), after transfection of miRNA mimic Let‐7b in the HUVEC supernatants.…”
Section: Epigenetic Changes In Pementioning
confidence: 98%
“…Furthermore, endothelin‐1 (ET‐1), an endothelium‐derived vasoconstrictor in SMCs, may function in the adaptive vasodilation during pregnancy 13 . In recent years, ET‐1 has been reported to be regulated post‐transcriptionally by various miRNAs 14 . For instance, miR‐199 is identified as a negative regulator of ET‐1 expression in human ECs 15 .…”
Section: Introductionmentioning
confidence: 99%